Hatched : dispatches from the backyard chicken movement - Warren, Gina G. (University of Washington Press, 2021)
""Chickens are a lot more mainstream than veganism and a little bit like kombucha: super weird twenty years ago, now somewhat popular and made even more so by logos, brands, and hashtags." So begins Gina Warren's deep-dive into the backyard chicken movement. Digging into its history and food politics, she provides a highly personal account of the movement's social and cultural motivations, the regulations it faces, and the ways that chicken owners build community. Weaving together interviews with urban agriculture advocates, entrepreneurs such as a $225 per hour "chicken consultant," animal rights campaigners, and a fabulous cross-section of chicken enthusiasts, Warren sheds light on Americans' complex relationship with animals-as guardians, companions, and eaters-and what it means to be a conscious eater. As Warren chronicles her own misadventures raising chickens, her pursuit of what's best for her own flock leads past chicken tutus and gourmet chicken treats and into serious attempts at sustainable eating, such as cooking insects and dumpster diving. The result is a fresh and charming story that speaks to backyard chicken owners, while also raising questions about sustainable farming, industrial agriculture, and our connections with the animals we love"--